Effect of stepwise nursing practice teaching mode on the success rate of first venipuncture among nursing interns (阶梯式护理实践教学模式对护理实习生首次静脉穿刺成功率的影响) - KONG Hua (孔华); XIN Liang (邢亮) (中西医结合护理)
Objective To explore the effect of stepwise nursing practice teaching mode on the success rate of the first venipuncture among nursing interns. Methods Totally 30 nursing interns were selected as the control group and the traditional teaching methods were adopted in July 2019. In the observation group, the step nursing practice teaching mode was adopted for another 30 nursing interns in July 2020. The success rate of the first venipuncture and patient satisfaction of the two groups were compared. Results The rate of first venipuncture in the observation group was higher than that in the control group , with a significant difference (P＜0. 05). The patient satisfaction degree in the observation group was higher than that in the control group, with a significant difference (P＜0. 01). Conclusion The stepwise nursing practice teaching mode can improve the success rate of the first venipuncture among nursing interns and increase patients' satisfaction with nursing service. (目的 探讨阶梯式护理实践教学模式对护理实习生首次静脉穿刺成功率的影响。方法 将2019年7月在科室实习的30名护士生设为对照组, 临床实习带教中采用传统教学方法。将2020年7月在科室实习的30名护士生定为观察组, 采用阶梯式护理实践教学模式教学。比较2组实习生首次静脉穿刺成功率, 评价患者对护理实习生的满意度。结果 观察组护理实习生首次穿刺成功率高于对照组, 差异有统计学意义(P<0. 05)。患者满意度观察组高于对照组, 差异有统计学意义(P<0. 01)。结论 阶梯式护理实践教学模式能够提高护理实习生首次静脉穿刺成功率, 提高患者满意度。)